Psychological Service in the Education System as a Phenomenon - Irina V. Dubrovina (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. The article highlights a relevant problem of upbringing students within modern school education as considered in the context of the role of interaction between psychology and pedagogy. The education system needs scientific psychological knowledge, since educational standards pay much attention to the issues of mental development of a growing person.